KPJ Seremban Specialist Hospital / Noradawiyah Yasmin Amran - Amran, Noradawiyah Yasmin (Bachelor of Information Science (Hons.) Records Management, 2015)
All bachelor degree students are compulsory to undergo industrial training for five month as part of their curriculum to complete their 2 years course for the Bachelor of Information Science (Hons) Record Management. During five month period of training, student will be supervied by two supervisor thats from the faculty and one from the organization. For my industrial training, I have done it at KPJ Seremban Specialist Hospital. It is a private hospital, KPJ Seremban Specialist Hospital was established in year 2003. KPJ Seremban Specialist Hospital with one of the country's best health system provides patients with access to the most advanced technology and leading edge medicine available. I was assigned to the Medical Record department which my supervisor is Mr Shaharin Izhar Abd Rahman. I was assigned with various tasks that are very out of the ordinary and useful for my education, lots of new experiences that I have gain from the KPJ Seremban Specialist Hospital. I learnt lots of things from the department, including retrieval of the record, managing, transferring, handling, disposal project and etc. It was an excellence journey in undertaking the task that has been given to me because I can apply the skill and experience at other places after finish with the industrial training. Some of the process were repeated daily accept for disposal and transferring the folders. Overall, it was an amazing experience to be in this department.